Voltammetric quantification of anti-hepatitis drug Adefovir in biological matrix and pharmaceutical formulation - Rajeev Jain; Ramkishor Sharma (Elsevier, 2012)
Electrochemical reduction behavior of Adefovir was studied using Hanging Mercury Drop Electrode (HMDE) in BrittonâRobinson (BR) buffer solution. Voltammetric study showed one well-defined reduction peak in the potential range â1.2 to â1.4Â V (vs. Ag/AgCl) due to reduction of C=N bond of the imidazole ring. Solid-phase extraction and protein-precipitation techniques were employed for extraction of Adefovir from human plasma. The proposed method allows quantification of Adefovir in human plasma over the concentration range 0.50â5.00Â Î¼g/mL with the detection limit 0.17Â Î¼g/mL, whereas in pharmaceutical formulation 0.25â2.25Â Î¼g/mL with the detection limit 0.08Â Î¼g/mL. Keywords: Voltammetry, Adefovir, Solid-phase extraction, Protein-precipitation, Human plasma, Pharmaceutical formulation